HbA1c Levels Increase in Patients with Non-Dipper Hypertension without Diabetes Mellitus - Akcay, Salaheddin; Kobat, Mehmet Ali; Inci, Fatih; Birkan, Zulfu; Yildiz, Mustafa; Dagli, Necati; Bilge, Ali Riza (Elsevier Science Inc, 2013)
[Abstract Not Available]
29th Turkish Cardiology Congress of the Turkish-Society-of-Cardiology (TSC) with International Participation -- OCT 26-29, 2013 -- Antalya, TURKEY